2013
DOI: 10.1007/s10156-013-0620-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of sitafloxacin 100 mg twice daily for 7 days for patients with non-gonococcal urethritis

Abstract: To clarify the clinical efficacy of STFX for patients with non-gonococcal urethritis (NGU), including chlamydial urethritis and Mycoplasma genitalium-positive urethritis, this study included male patients with NGU who were 20 years old or older. The pathogens, including Chlamydia trachomatis, M. genitalium and Ureaplasma urealyticum, were detected by nucleic acid amplification tests and the patients were treated with sitafloxacin 100 mg twice daily for 7 days. Microbiological and clinical efficacies were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 23 publications
1
27
0
3
Order By: Relevance
“…Finally, sitafloxacin has additionally high activity against Chlamydia trachomatis and Mycoplasma genitalium , frequent aetiological agents of non‐gonococcal urethritis and cervicitis. In two studies published in 2012 and 2013, sitafloxacin 100 mg twice daily orally for 7 days eradicated 95.7–100% and 93.8–100% of C. trachomatis and M. genitalium infections, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, sitafloxacin has additionally high activity against Chlamydia trachomatis and Mycoplasma genitalium , frequent aetiological agents of non‐gonococcal urethritis and cervicitis. In two studies published in 2012 and 2013, sitafloxacin 100 mg twice daily orally for 7 days eradicated 95.7–100% and 93.8–100% of C. trachomatis and M. genitalium infections, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Some quinolones, such as moxifloxacin, have potent activity in vivo and in vitro against MG, and treatment with moxifloxacin is considered as an effective second-line treatment for azithromycin-resistant, persistent or recurrent MG infections [54,71]. The antibacterial activities of the quinolones may be due to their inhibitory activities against bacterial type II topoisomerases, such as DNA gyrase and topoisomerase IV (Table 6) [54,[67][68][69]71,72].…”
Section: ) Topoisomerase Iiamentioning
confidence: 99%
“…The antibacterial activities of the quinolones may be due to their inhibitory activities against bacterial type II topoisomerases, such as DNA gyrase and topoisomerase IV (Table 6) [54,[67][68][69]71,72]. Therefore, it has been reported that mutations in the quinolone resistance-determining regions of the type II topoisomerases contribute to quinolone resistance in various bacterial species, including MG [67][68][69].…”
Section: ) Topoisomerase Iiamentioning
confidence: 99%
“…[7]. Bei Zunahme von Resistenzbildungen muss der Stellenwert von anderen Medikamenten wie Sitafloxacin oder Gatifloxacin weiter untersucht werden [10,27], um eine drohende Unbehandelbarkeit von M. genitalis abzuwenden [28].…”
Section: Schlüsselwörterunclassified